INTERDEPENDENCE OF HEALTH CHARACTERISTICS AND PERSONALITY TRAITS OF STUDENTS IN THE DYNAMICS OF TRAINING IN A MEDICAL INSTITUTION OF HIGHER EDUCATION - Serheta, Ihor; Stoyan, Natalis (Collection of scientific papers «ΛΌГOΣ», 2025)
The initial component of the development of effective health-preserving technologies is the establishment of patterns of interdependence between health characteristics and indicators of the development of psychophysiological functions and personality traits of pupils and students in the conditions of a MEDICAL institution of higher education